2000
DOI: 10.1097/00005392-200012000-00083
|View full text |Cite
|
Sign up to set email alerts
|

PROGNOSTIC VALUE OF CELL CYCLE PROTEINS p27kip1 AND MIB-1, AND THE CELL ADHESION PROTEIN CD44s IN SURGICALLY TREATED PATIENTS WITH PROSTATE CANCER

Abstract: Reduced p27(kip1) expression is an independent predictor of poor outcome in prostate cancer, while MIB-1 is not. Decreased expression of CD44s yields additional information in predicting clinical recurrence. These tissue markers may identify patients at risk for disease recurrence after retropubic radical prostatectomy who may benefit from adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…This is contradictory to most tumors, where a low p27 Kip1 is associated with poor prognosis, e.g., colorectal, epithelial, ovarian, breast, gastric, Barrett's, esophageal, non-small cell lung, and prostatic carcinomas (18 -21, 32-37). The findings are, however, consistent with previous evidence that p27 Kip1 is often expressed at relatively high levels in human cancer cell lines, which are additionally characterized by increased the expression of cyclin D1 or cyclin E (38,39). Also, high levels of p27 Kip1 are associated with poor survival in invasive cervical carcinoma (16) High proliferative activity, as defined by expression of the Ki-67 analysis (MIB-1) antibody, has been shown to correlate with reduced p27 Kip1 in lymphoid neoplasms, carcinoma of the oral cavity, and endocrine tumors, including pituitary, thyroid, and parathyroid gland hyperplasia (14, 40 -43).…”
Section: Discussionsupporting
confidence: 91%
“…This is contradictory to most tumors, where a low p27 Kip1 is associated with poor prognosis, e.g., colorectal, epithelial, ovarian, breast, gastric, Barrett's, esophageal, non-small cell lung, and prostatic carcinomas (18 -21, 32-37). The findings are, however, consistent with previous evidence that p27 Kip1 is often expressed at relatively high levels in human cancer cell lines, which are additionally characterized by increased the expression of cyclin D1 or cyclin E (38,39). Also, high levels of p27 Kip1 are associated with poor survival in invasive cervical carcinoma (16) High proliferative activity, as defined by expression of the Ki-67 analysis (MIB-1) antibody, has been shown to correlate with reduced p27 Kip1 in lymphoid neoplasms, carcinoma of the oral cavity, and endocrine tumors, including pituitary, thyroid, and parathyroid gland hyperplasia (14, 40 -43).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the identification of membrane antigens or biomarkers using immunohistochemical techniques has become important for the diagnosis, prognosis, classification and treatment evaluation. It was shown that it is possible to identify predictive markers for biochemical failure [3][4][5], disease recurrence and patient survival after radical prostatectomy [4,6,7]. However, there remains conflicting evidence regarding prognostic influence of an individual marker.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the proliferation fraction of primary PC, as assessed by Ki-67 (MIB-1) expression was associated with the grade or stage of prostatic cancer and clinical outcome of patients after radical prostatectomy [1,5,10]. However, other authors [7,11] could not see prognostic impact of Ki-67 proliferative activity in their patients' set.…”
Section: Introductionmentioning
confidence: 99%
“…When both a non-invasive and invasive component coexist in the tumour, loss of p27 KIP1 protein is detected in both carcinoma in situ and invasive tumour, suggesting that events leading to deregulation of p27 KIP1 protein may precede invasion 59 . For example, p27 KIP1 protein is reduced in benign prostatic hypertrophy, a hyperplastic premalignant prostatic neoplasm [65][66][67] . Study of prostate carcinoma also showed variable degrees of reduction in p27 KIP1 staining was frequently observed in the prostatic intraepithelial neoplasia adjacent to invasive carcinoma 66 .…”
Section: P27mentioning
confidence: 99%